Stagnated Liberalization, Long-term Convergence, and Index Methodology: Three Lessons from the CITRIX Citizenship Policy Dataset - Samuel D. Schmid (Global Policy, 2021)
In this article, I present the second version of the Citizenship Regime Inclusiveness Index (CITRIX 2.0). It measures the inclusiveness of regulations for immigrants' access to citizenship across 23 OECD countries from 1980 to 2019, zooming in on four essential policy components: conditions regarding (1) birthright; (2) residence; (3) renunciation; and (4) integration. While explaining the construction of the dataset, I advance a synthetic approach to index methodology. The main idea of this approach is to use statistical dimensionality tests to validate deductively specified additive concept structures. This is the first lesson we can learn from CITRIX. After validating the index in terms of content, dimensionality, and convergence, a short empirical analysis presents two additional lessons. First, after two cycles of liberalization and subsequent restrictive turns, mostly in integration conditions, aggregate citizenship policy inclusiveness has stagnated, but liberalized overall. 2003 marks the peak of liberalization. Second, there has been long-term convergence constituted by two phases of convergence with one diverging phase in between. I conclude that liberalization is more limited, and convergence more pronounced, than often assumed. CITRIX offers a versatile toolbox for future research to explore citizenship policies and their correlates. Regular updates are planned.
Keywords: 320